An Assessment of Female Prisoners’ Perception of the Accessibility of Quality Healthcare: A Survey in the Kumasi Central Prisons, Ghana - Sarpong, A. A.; Otupiri, Easmon; Yeboah‑Awudzi K ,; Osei-Yeboah, J.; Berchie, G. O.; Ephraim, R. K.D. (Annals of Medical and Health Sciences Research, 2023)
This is an article published in Annals of Medical and Health Sciences Research, May-Jun 2015, Vol 5 ,Issue 3